THE ROLE OF OZONE THERAPY IN THE REHABILITATION OF PATIENTS WITH CORONARY HEART DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
contribute to the effectiveness of the main course of treatment. Ionized oxygen has a profound stabilizing effect on the metabolic processes in the tissues of the heart and blood vessels. With the help of ozone therapy sessions, it is possible to significantly improve the quality of life for a sick person. The problem of treating patients with coronary heart disease (CHD) is urgent due to the increasing frequency of the disease. CHD is a disease of the heart muscle caused by a violation of the balance between coronary blood flow and the metabolic needs of the heart muscle. In recent years, medical ozone has been used to normalize the oxygen supply of tissues. By changing the structure of membrane lipids, ozone increases the deformability of erythrocytes and thereby improves the rheological properties of blood. It has a vasodilating effect, significantly improves the oxygen output by oxyhemoglobin.